The study of employees’ personality and its relationship with absenteeism in tertiary education. - Chah, Hong Teng; Foo, Shi Ying; Low, Pai Cheng; Ooi, Lee Peng; Wong, Siew Ming (2011)
Nowadays Malaysia is facing higher absenteeism rate in which the cost of lost work time is substantially higher than employee salary when perfect replacement are not available to replace employees absenteeism. Therefore, in solving these problems, several researches had been conducted in tertiary education to enhance employee’s morale and ensure quality service provided by employees The main purpose of this research is to determine whether there is a significant relationship between Big Five Model (Conscientious, Extroversion, Emotional Stability, Openness to Experience, Agreeableness) and employers’ absenteeism. This research was targeted to respondents in Universiti Tunku Abdul Rahman (UTAR), Perak Campus due to the convenience to distribute and collect back the questionnaires. Printed questionnaire has been used instead of electronic questionnaire in order to explain any double arise by respondents. 200 questionnaires have been distributed however only 165 questionnaires were collected back. Subsequently, the data was tested and analyzed by using the Statistical Package for Social Science (SPSS). Through the research project result, Extroversion tends to have positive relationship with absenteeism. In contrast, Conscientious and Emotional Stability tend to have negative relationship with absenteeism.